O consumo da pornografia pelas mulheres : usos e gratificações - Santos, Marília Souza (2021)
The internet has brought to pornography a new possibility of consumption and, consequently, an increase in women accessing the content, for free or even for a fee. This phenomenon known as “domestication of pornography” (ABREU, 1997) opened a loophole so that the gender focus could be included in studies on the consumption of pornography. Once seen as derogatory and violent towards the role of women, new models of pornographic productions have been distributed throughout the industry, especially from the beginning of the 2000s, with a new approach to image and female pleasure. From the profusion of this new dynamic and the consolidation of a captive target audience, our interest in understanding the uses and gratifications of pornography by women arose. Our investigation starts from the theoretical approach of Uses and Gratifications with the use of Grounded Theory, or Grounded Theory, as a methodological research resource. Through 13 online interviews with women of diferente states, ages, occupations and sexual orientation, motives for learning and managing mood were highlighted for the consumption of pornography by women. Therefore, our study proposal aims to build a hypothetical-theoretical formulation capable of explaining the main attractive factors of this product among women today.